A pre-and post-training assessment of the halal executive training program towards upholding halal food supply chain/ Nina Naquiah Ahmad Nizar ... [et al.] - Ahmad Nizar, Nina Naquiah; Taib, Mohd Nasir; Bujang, Aishah; Zainal Abidin, Siti Aimi Sarah; Rahmat, Abdul Khabir (Universiti Teknologi MARA Selangor, 2022)
The global halal business is projected to be valued at USD 2.3 trillion to cater to the demands and preferences of the world's 1.7 billion Muslim consumers. It establishes the worldwide halal market as a powerful commercial arena and a critical developing sector. The importance of education, especially halal executive training in this competitive industry, should not be disregarded. Therefore, this article embarked on the interrelated outcomes of halal executive training programs among halal executive training participants pre- and post-training. Attention is given to the knowledge gained during training and halal executives' tasks followed by the impact of the halal executive training program in assisting the halal food sector in ensuring an excellent halal supply chain.